Quorum and Light Signals Modulate Acetoin/Butanediol Catabolism in Acinetobacter spp. - Tuttobene, Marisel Romina; Fernández-García, Laura; Blasco, Lucía; Cribb, Pamela; Ambroa, Anton; Müller, Gabriela Leticia; Fernández-Cuenca, Felipe; Bleriot, Inés; Rodríguez, Ramiro Esteban; Barbosa, Beatriz G. V.; Lopez-Rojas, Rafael; Trastoy, Rocío; et al. (Frontiers in Microbiology, 2019)
Acinetobacter spp. are found in all environments on earth due to their extraordinary capacity to survive in the presence of physical and chemical stressors. In this study, we analyzed global gene expression in airborne Acinetobacter sp. strain 5-2Ac02 isolated from hospital environment in response to quorum network modulators, and found that they induced the expression of genes of the acetoin/butanediol catabolism, volatile compounds shown to mediate interkingdom interactions. Interestingly, the acoN gene, annotated as a putative transcriptional regulator, was truncated in the downstream regulatory region of the induced acetoin/butanediol cluster in Acinetobacter sp. strain 5-2Ac02, and its functioning as a negative regulator of this cluster integrating quorum signals was confirmed in A. baumannii ATCC 17978. Moreover, we show that the acetoin catabolism is also induced by light, and provide insights into the light transduction mechanism by showing that the photoreceptor BlsA interacts with and antagonizes the functioning of AcoN in A. baumannii, integrating also a temperature signal. The data support a model in which BlsA interacts with and likely sequesters AcoN at this condition, relieving acetoin catabolic genes from repression, and leading to better growth under blue light. This photoregulation depends on temperature, occurring at 23 but not at 30ºC. BlsA is thus a dual regulator, modulating different transcriptional regulators in the dark but also under blue light, representing thus a novel concept. The overall data shows that quorum modulators as well as light regulate the acetoin catabolic cluster, providing a better understanding of environmental as well as clinical bacteria.